Dampak Pernikahan Usia Muda terhadap Keharmonisan Keluarga Perspektif Hukum Islam - Sarah Azami; Abi Yazid Albustomi; Ananda Putra Syach Fadhilah; Muhammad Said Ramdan Hardiana; Hikmatullah Hikmatullah (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2026)
Marriage at an early age remains widespread, especially among communities with limited education and financial resources. This study aims to analyze the impact of early marriage on harmony in household life. The research model we employed was a library research design. The approach used was descriptive qualitative through literature review, referring to scholarly sources and secondary data from reputable journals published in the last five years. Findings indicate that the mental unreadiness of both parties (husband and wife) who marry at an early age can lead to instability in household life and increase the risk of marital failure or reduced family harmony. Young couples commonly face challenges in maintaining healthy communication, making joint decisions, and coping with financial pressures, all of which contribute to domestic conflict. In addition, emotional immaturity and limited life experience are also primary causes of disharmony within the family. Therefore, there is a need to improve education and public awareness about the importance of age maturity and mental readiness before marriage in order to create stable and harmonious households. Thus, it is necessary to increase education and public awareness about the importance of age maturity and mental readiness before marriage, in order to create a stable and harmonious household.